1947
DOI: 10.1115/1.4017598
|View full text |Cite
|
Sign up to set email alerts
|

Explanation of Longitudinal Shrinkage of Wood Based on Interconnected Chain-Molecule Concept of Cell-Wall Structure

Abstract: This paper demonstrates that the following four factors exert a significant influence on the longitudinal shrinkage-moisture content relationship of wood: (a) The interconnection of chain molecules; (b) fibril angle; (c) the cellulose chain-molecule length; (d) the microcapillary width. A mathematical demonstration is given to check the validity of the shrinkage theory advanced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1949
1949
2006
2006

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several explanations have been put forward as to the causes of nonlinearity in the longitudinal shrinking process. [7][8][9][10] For example, Sadoh and Kingston 10 concluded that nonlinearity is due to decreased slipping of the chain molecules against one another, and that this decrease is caused, in turn, by increasing interchain molecular bonding with reduced moisture content. On the other hand, according to Meylan, 7 it was assumed that the only cause of nonlinearity is a change in the elastic constants as the moisture content changes.…”
Section: Introductionmentioning
confidence: 99%
“…Several explanations have been put forward as to the causes of nonlinearity in the longitudinal shrinking process. [7][8][9][10] For example, Sadoh and Kingston 10 concluded that nonlinearity is due to decreased slipping of the chain molecules against one another, and that this decrease is caused, in turn, by increasing interchain molecular bonding with reduced moisture content. On the other hand, according to Meylan, 7 it was assumed that the only cause of nonlinearity is a change in the elastic constants as the moisture content changes.…”
Section: Introductionmentioning
confidence: 99%